2011
DOI: 10.1103/physrevb.84.144430
|View full text |Cite
|
Sign up to set email alerts
|

Morphology influence on nanoscale magnetism of Co nanoparticles: Experimental and theoretical aspects of exchange bias

Abstract: Co-based nanostructures ranging from core/shell to hollow nanoparticles were prepared by varying the reaction time and the chemical environment during the thermal decomposition of Co 2 (CO) 8 . Both structural characterization and kinetic model simulation illustrate that the diffusivities of cobalt and oxygen determine the growth ratio and the final morphology of the nanoparticles. Exchange coupling between Co and Co-oxide in core/shell nanoparticles induced a shift of field-cooled hysteresis loops that is pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 41 publications
6
62
0
Order By: Relevance
“…Remarkably, although the Néel temperature of Co 3 O 4 is below 40 K, the loop shifts persist up to ∼250 K or above, demonstrating the robustness of the exchange coupling between core and shell and the persistence of EB effects up to almost room temperature. Previous reports on the EB effect in systems with coexisting Co/Co 3 O 4 phases indicated that a minor presence of CoO led to the persistence of EB much above its T N [24][25][26][27][28][29]. Analogously, persistence of EB above T N was also observed in Co/FeF 2 [56] and was explained by retention of short range magnetic ordering above T N .…”
Section: Magnetic Characterizationsupporting
confidence: 49%
See 4 more Smart Citations
“…Remarkably, although the Néel temperature of Co 3 O 4 is below 40 K, the loop shifts persist up to ∼250 K or above, demonstrating the robustness of the exchange coupling between core and shell and the persistence of EB effects up to almost room temperature. Previous reports on the EB effect in systems with coexisting Co/Co 3 O 4 phases indicated that a minor presence of CoO led to the persistence of EB much above its T N [24][25][26][27][28][29]. Analogously, persistence of EB above T N was also observed in Co/FeF 2 [56] and was explained by retention of short range magnetic ordering above T N .…”
Section: Magnetic Characterizationsupporting
confidence: 49%
“…With the increase of the oxide component at the shell, the loop shapes become more elongated with higher closure fields [26,39] and a high field linear component with increasing contribution. This high field susceptibility can be ascribed to the contribution of uncompensated spins in the antiferromagnetic shell and core/shell interface [43][44][45] as it dies off at temperatures higher than T N of Co 3 O 4 .…”
Section: Magnetic Characterizationmentioning
confidence: 99%
See 3 more Smart Citations